2022
DOI: 10.3390/ijms231810742
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Breast Cancer in Mexican Women with Obesity as a Risk Factor

Abstract: Purpose. Adipose tissue in overweight and obesity shows metabolic imbalance in the function of adipocytes and macrophages, this leads to altered regulation of hunger, lipid storage, and chronic inflammation possibly related to the development of breast cancer. Methods. The study was retrospective of 653 breast cancer patients treated at a tertiary care hospital. Histopathology, hormone receptors, grade, clinical stage, clinical biometry analysis, CEA and CA 15-3 antigens were analyzed. The analyses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The study population was found to be 73% of women with overweight and obesity and who were considered a risk factor for treatment and chronic diseases [3].…”
Section: Percentage With Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…The study population was found to be 73% of women with overweight and obesity and who were considered a risk factor for treatment and chronic diseases [3].…”
Section: Percentage With Obesitymentioning
confidence: 99%
“…The secondary effects of the damage depend on individual sensitivity, the treatment regimen, and the dosing. Human Epidermal Growth Factor Receptor Type 2-positive (HER2+) breast cancer presents in 15% of Mexican women and treatment of the latter is based on hormone therapy with Tratuzumab [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that by the year 2022, worldwide, the numbers of breast cancer cases were estimated at 2.2 million cases, with 685,000 deaths from this cancer. 4 Despite advances in diagnosis and treatment, 45% of the global incidence occurs in developing countries, representing 55% of all deaths. In Mexico, Globocan Department of Plastic and Reconstructive Surgery, Hospital General de México "Dr. Eduardo Licéaga", México City, México estimates that the incidence and mortality of breast cancer is 39.5 and 9.9 cases per 100,000, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary effects of the damage depend on individual sensitivity, the treatment regimen, and the dosing. Human Epidermal Growth Factor Receptor Type 2-positive (HER2+) breast cancer presents in 15% of Mexican women [3] and treatment of the latter is based on hormone therapy with Tratuzumab [4]. Cardiological control is necessary in patients, above all when the CT is combined with anthracyclines, requiring the assessment of the ventricular function and of the function of harmful proteins [5,6] within the care protocols.…”
Section: Introductionmentioning
confidence: 99%

Post-chemotherapy Cardiotoxicity in Women With Breast Cancer

Maldonado-Vega,
Cejudo-Arteaga,
Ramirez-Reyes
et al. 2023
Preprint
Self Cite